2005
DOI: 10.1177/0272989x04273140
|View full text |Cite
|
Sign up to set email alerts
|

Health State Utilities for Childhood Attention-Deficit/Hyperactivity Disorder Based on Parent Preferences in the United Kingdom

Abstract: This UK-based study suggests that parent SG interviews are a valid method for obtaining utilities for child ADHD-related health states. The utilities obtained in this study would be appropriate for use in a cost-utility analysis evaluating the costs and benefits of childhood ADHD treatments in the United Kingdom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
69
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 44 publications
(56 reference statements)
1
69
1
Order By: Relevance
“…This duration was evaluated in the pilot study described below, and patients reported no difficulties. The health state duration of 1 month has consistently been found to be acceptable to patients in previous utility studies [7,[43][44][45]. As the health states were being developed, drafts were presented to a physician who is an endocrinologist and diabetes specialist.…”
Section: Development Of Health Statesmentioning
confidence: 99%
See 3 more Smart Citations
“…This duration was evaluated in the pilot study described below, and patients reported no difficulties. The health state duration of 1 month has consistently been found to be acceptable to patients in previous utility studies [7,[43][44][45]. As the health states were being developed, drafts were presented to a physician who is an endocrinologist and diabetes specialist.…”
Section: Development Of Health Statesmentioning
confidence: 99%
“…The utility interview procedures have been established in many previous studies that assessed patient preferences Diabetes injection utilities 221 relating to medical conditions [7,41,[43][44][45][46]. The first step was a visual analog scale (VAS) exercise intended to familiarize the patients with the health states.…”
Section: Utility Interview Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…This duration was evaluated as part of the pilot study described below, and patients reported no difficulties. The health state duration of 1 month has also been used in several previous utility studies, and it has consistently been found to be acceptable to patients [45][46][47].…”
Section: Development Of Health Statesmentioning
confidence: 99%